2019
DOI: 10.3390/ijms20133242
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Surface-Active Protein Extracted from a Marine Strain of Penicillium chrysogenum

Abstract: Marine microorganisms represent a reservoir of new promising secondary metabolites. Surface-active proteins with good emulsification activity can be isolated from fungal species that inhabit the marine environment and can be promising candidates for different biotechnological applications. In this study a novel surface-active protein, named Sap-Pc, was purified from a marine strain of Penicillium chrysogenum. The effect of salt concentration and temperature on protein production was analyzed, and a purificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
1
9
0
1
Order By: Relevance
“…Therefore, as a first approach, the ability of both proteins to stabilize emulsions was verified. Indeed, the obtained E 24 values were comparable to those of other proteins and to commercially available surfactants analyzed in the same way [19,23].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Therefore, as a first approach, the ability of both proteins to stabilize emulsions was verified. Indeed, the obtained E 24 values were comparable to those of other proteins and to commercially available surfactants analyzed in the same way [19,23].…”
Section: Discussionsupporting
confidence: 76%
“…We also analyzed the surface tension reduction of these CPs and unexpectedly observed that ThCP behaves as a good BS, beyond being a good BE. Indeed, the surface tension value reached in the presence of ThCP was much lower than those of AtCP and of Sap-Pc, another BE protein recently purified from a marine strain of Penicillium chrysogenum, measured in comparable conditions [23].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A comparable two‐stage decrease in surface tension was observed in the surface‐active Sap‐Pc protein from a marine strain of Penicillium chrysogenum . [ 28 ] Altogether these results indicate for the first time, at least to our knowledge, that the p‐gliadin is composed of self‐associated peptides that are active at the water/air interface. These C.A.C values are much below than the 1 mg mL −1 usually employed in biomedical research, which implies that large p‐gliadin supramolecular structures should be present in vitro studies.…”
Section: Resultsmentioning
confidence: 65%
“…Marine proteins are mainly isolated from marine organisms such as sponges [8], sea squirts [9], mollusks [10], algae [11], marine fungi [12], and marine strain [13]. A large number of investigations have shown that marine proteins exert good antitumor effects.…”
Section: Introductionmentioning
confidence: 99%